A Knowledge Management and Decision Support Model for Enterprises. (26th October 2011) - Ribino, Patrizia; Augello, Agnese; Lo Re, Giuseppe; Gaglio, Salvatore
Abstract : We propose a novel knowledge management system (KMS) for enterprises. Our system exploits two different approaches for knowledge representation and reasoning: a document-based approach based on data-driven creation of a semantic space and an ontology-based model. Furthermore, we provide an expert system capable of supporting the enterprise decisional processes and a semantic engine which performs intelligent search on the enterprise knowledge bases. The decision support process exploits the Bayesian networks model to improve business planning process when performed under uncertainty.